Population pharmacokinetics-pharmacodynamics of fondaparinux in dialysis-dependent chronic kidney disease patients undergoing chronic renal replacement therapy - Michaličková, Danica; Hartinger, Jan; Hladinová, Zuzana; Bednářová, Vladimíra; Szonowská, Barbora; Polakovič, Vladimír; Matthios, Andreas; Tesař, Vladimír; Slanař, Ondřej; Krekels, Elke H J (European journal of clinical pharmacology, 2022)
PURPOSE: Data on the anti-Xa efficacy of fondaparinux in dialysis-dependent chronic kidney disease (DD-CKD) patients are scarce. This study characterizes the pharmacokinetics (PK) and pharmacodynamics (PD) of fondaparinux in DD-CKD patients undergoing renal replacement therapy (RRT), to assess dosing strategies. METHODS: A retrospective, observational study was conducted using data on anti-Xa activity (112 samples) from 12 (3 male and 9 female) DD-CKD patients (median (IQR) age 71 years (63-88), weight 73 kg (59-98.5)). Eleven patients underwent high-flux or low-flux hemodialysis (HD) and one patient underwent peritoneal dialysis. Three patients were also treated with therapeutic plasma exchange (TPE). A non-linear mixed effects analysis was performed using NONMEM 7.3.0. RESULTS: The lab-specific slope of the relationship between fondaparinux concentration and anti-Xa levels was 1.18 IU/μg. In a one-compartment model, clearance (CL) and volume of distribution (Vd) were 0.05289 L/h and 5.55 L, respectively. High-flux HD was found to increase the CL of fondaparinux 2.26 times. TPE also considerably increased CL, but the fold-change could not be accurately estimated. Low-flux HD and peritoneal dialysis did not impact PK parameters. CONCLUSIONS: Model-based simulations showed that standard dosing (2.5 mg three times weekly before HD) results in a median anti-Xa activity of 0.55 IU/mL and 0.98 IU/mL, pre- and post-low-flux HD, respectively. In patients undergoing high-flux HD, these values are approximately 27% lower. Additional caution is warranted with TPE, as this treatment can reduce anti-Xa activity even further.
Keywords: Female; Age Factors; ženské pohlaví; Renal Insufficiency, Chronic; věkové faktory; fondaparinux; lidé; Renal Replacement Therapy; náhrada funkce ledvin; Aged, 80 and over; chronická renální insuficience; tělesná hmotnost; retrospektivní studie; Male; Factor Xa Inhibitors; Aged; inhibitory faktoru Xa; Fondaparinux; Body Weight; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Retrospective Studies; Middle Aged; Humans